Molecular Imprinted of Nylon 6 for Selective Separation of Procaine by Solid-Phase Extraction - Muhammed Emad Abood; Sumayha Muhammed Abbas (Universitas Gadjah Mada, 2021)
The study is based on the selective binding ability of the drug compound procaine (PRO) on a surface imprinted with nylon 6 (N6) polymer. Physical characterization of the polymer template was performed by X-ray diffraction and DSC thermal analysis. The imprinted polymer showed a high adsorption capacity to trap procaine (237 µg/g) and excellent recognition ability with an imprinted factor equal to 3.2. The method was applied to an extraction column simulating a solid-phase extraction to separate the drug compound in the presence of tinoxicam and nucleosimide separately and in a mixture of them with a recovery rate more than the presence of tinoxicam and nucleosimide separately and in a mixture of them with a recovery rate of more than 82%. Separation efficiency and excellent selectivity for procaine were ensured using a mixed solution injected into an HPLC technique consisting of a C18 column with a mobile phase mixture of water-acetonitrile (75:25) at pH 3.3. The study of drug control using an imprinted polymer with procaine compound showed that the complete drug release process is faster at pH1 in a maximum period of 80 min. The proposed method was successfully applied on some of the available pharmaceuticals, and it showed high selectivity for the separation of PRO, RE % was < 1.18, and RSD was less than 0.447.